A square meal : a culinary history of the Great Depression - Ziegelman, Jane; Coe, Andrew (Andy) (Harper, 2016)
"From the author of the acclaimed 97 Orchard and her husband, a culinary historian, an in-depth exploration of the greatest food crisis the nation has ever faced--the Great Depression--and how it transformed America's culinary culture. The decade-long Great Depression, a period of shifts in the country's political and social landscape, forever changed the way America eats. Before 1929, America's relationship with food was defined by abundance. But the collapse of the economy, in both urban and rural America, left a quarter of all Americans out of work and undernourished--shattering long-held assumptions about the limitlessness of the national larder. In 1933, as women struggled to feed their families, President Roosevelt reversed long-standing biases toward government-sponsored 'food charity.' For the first time in American history, the federal government assumed, for a while, responsibility for feeding its citizens. The effects were widespread. Championed by Eleanor Roosevelt, 'home economists' who had long fought to bring science into the kitchen rose to national stature. Tapping into America's long-standing ambivalence toward culinary enjoyment, they imposed their vision of a sturdy, utilitarian cuisine on the American dinner table. Through the Bureau of Home Economics, these women led a sweeping campaign to instill dietary recommendations, the forerunners of today's Dietary Guidelines for Americans. At the same time, rising food conglomerates introduced packaged and processed foods that gave rise to a new American cuisine based on speed and convenience. This movement toward a homogenized national cuisine sparked a revival of American regional cooking. In the ensuing decades, the tension between local traditions and culinary science has defined our national cuisine--a battle that continues today. A Square Meal examines the impact of economic contraction and environmental disaster on how Americans ate then--and the lessons and insights those experiences may hold for us today. A Square Meal features 25 black-and-white photographs"--